2021
DOI: 10.3389/fgene.2021.649599
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Associated Microbiota Composition Across Domestic Animals

Abstract: Domestic animals represent important resources for understanding shared mechanisms underlying complex natural diseases that arise due to both genetic and environmental factors. Intestinal inflammation, particularly inflammatory bowel disease (IBD), is a significant health challenge in humans and domestic animals. While the etiology of IBD is multifactorial, imbalance of symbiotic gut microbiota has been hypothesized to play a central role in disease pathophysiology. Advances in genomic sequencing and analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 84 publications
(119 reference statements)
3
7
0
Order By: Relevance
“…In this study, the dominant phyla found in the donkey fecal microbiota in all groups were Firmicutes and Bacteroidetes ( Figure 3A ), consistent with previous studies showing that the most abundant phyla were Firmicutes and Bacteroidetes with respect to the breeding stages ( Kong et al, 2016 ; Cheng et al, 2018 ; Shao et al, 2020 ). In the equine gut, Firmicutes generally displays the highest relative abundance, followed by Bacteroidetes ( Venable et al, 2016 ; Hashimoto-Hill and Alenghat, 2021 ), which is similar to our study. Furthermore, we found that the relative abundance of the phylum Firmicutes was highest in EP, whereas Bacteroidetes showed the opposite result.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the dominant phyla found in the donkey fecal microbiota in all groups were Firmicutes and Bacteroidetes ( Figure 3A ), consistent with previous studies showing that the most abundant phyla were Firmicutes and Bacteroidetes with respect to the breeding stages ( Kong et al, 2016 ; Cheng et al, 2018 ; Shao et al, 2020 ). In the equine gut, Firmicutes generally displays the highest relative abundance, followed by Bacteroidetes ( Venable et al, 2016 ; Hashimoto-Hill and Alenghat, 2021 ), which is similar to our study. Furthermore, we found that the relative abundance of the phylum Firmicutes was highest in EP, whereas Bacteroidetes showed the opposite result.…”
Section: Discussionsupporting
confidence: 91%
“…Polyketide-synthesizing bacteria are strongly associated with chronic intestinal inflammation ( Arthur et al, 2012 ). Moreover, in post-weaning diarrhea pigs, the increased abundance of the type II polyketide product biosynthesis pathway might be responsible for the increased inflammatory response ( Dou et al, 2017 ; Hashimoto-Hill and Alenghat, 2021 ). However, stilbenoid diarylheptanoid and gingerol, secondary metabolites of plants, have been reported to have anti-inflammatory or anticancer activities ( Park et al, 1998 ; Yadav et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased abundance of several members of the Bacteroidetes such as ASVs belonging to the genera Bacteroides and Pevotella detected in this study have been previously reported in IBD in dogs and human (Hashimoto-Hill and Alenghat, 2021;Lee and Chang, 2021). Increase in other bacterial types such as Clostridium, Escherichia-Shigella and Streptococcus has been also previously reported (Honneffer et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Our study proposes a new nutritional strategy for improving intestinal health of canine. Furthermore, as dogs and humans exhibit high structural and functional similarities in their microbiome, and their IBD symptoms share similar features, this study may have the potential to extend to improving human gut health 18,19 …”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, as dogs and humans exhibit high structural and functional similarities in their microbiome, and their IBD symptoms share similar features, this study may have the potential to extend to improving human gut health. 18,19 function on canine IBD is mediated by altering gut microbial composition and improving bile acid metabolism. This study proposes a natural polyphenol-based dietary strategy for improving canine intestinal health.…”
Section: Introductionmentioning
confidence: 99%